Concentration of Herpesviruses - Smith, Janet Duyckinck (1973)
A method has been developed for the concentration of herpesviruses by negative pressure ultrafiltration through dialysis tubing. The procedure results in high titer concentrates of unaggregated, morphologically intact viral particles with a virtually quantitative recovery of infectivity.